Enthalpy of sublimation/vaporization of trans-cyclohexyl-1,4-diamine and cis-cyclohexyl-1,2-diamine - Tomé, Luciana I. N. (2007)
The molar enthalpy of sublimation, , of trans-cyclohexyl-1,4-diamine and the molar enthalpy of vaporization, , of cis-cyclohexyl-1,2-diamine, at the temperature 298.15 K, were determined by calorimetry. was obtained for the trans-isomer and for the cis form. The molar enthalpy of fusion of the first compound, at T = 342.1 K, was determined by differential scanning calorimetry. The molar enthalpy of vaporization of the 1,4-isomer was estimated by combining the value of the enthalpy of sublimation with that of the enthalpy of fusion.